Renewable energy from the oceans : from wave, tidal and gradient systems to offshore wind and solar - Coiro, Domenico P.; Sant, Tonio (IET energy engineering series ;, 2019)
The book comprises of 12 chapters and presents an overview of the development of ocean energy technologies, renewable energy resources and latest emerging trends. It presents a broad perspective, covering important aspects from energy conversion, installation, operation and planning to grid connection and storage. Latest literature sources in various relevant fields are presented together with theoretical fundamentals for system engineering analysis.